Användning av rötrest från kombinerad etanol och biogasproduktion : en jämförelse mellan tre alternativ - Albertsson, Isak (SLU/Dept. of Energy and Technology, 2008)
Scandinavian Biogas is involved in the planning of a combined ethanol and biogas factory in Karlskoga, Sweden. Besides biogas and ethanol large amounts of digester residues will be produced, about 450 000 liquid tonnes residue (~7,3 % Dry Substance( DS)). The objective of this thesis was to investigate possible uses of the residue from the biogas production process ScandgasEthanol developed by Scandinavian Biogas, and to derive a methodological approach how to evaluate and compare handling systems. Three systems where proposed and compared in this thesis; spreading of the untreated residue as fertilizer (system 1), dewatering to a higher DS content to reduce transportation before spreading as fertilizer (system 2) and production of a solid fuel by dewatering and drying the residue (system 3). The general conditions for the proposed systems were investigated in terms of practical viability, economical aspects, environmental impact and energy inputs/outputs. The method was exemplified by the specific case of Karlskoga. The methodological framework for the environmental and energy analysis was life cycle analysis theory. The residue was assumed to replace mineral fertilizers or solid fuels. Each system was credited for avoided environmental impact and energy from avoided production/ use of fertilizer/fuel. Advantages for system 1 were the possibility to market the residue as a certified organic fertilizer whereby the plant nutrients represents a relatively high economical value, and a reduction in global warming emissions due to avoided use of mineral fertilizer. The downsides are large demand for transports and spreading areas. Transport demand is reduced in system 2, but the dewatering involves process chemicals that are both expensive compared to the value of the recycled nutrients and precludes the market for certified fertilizers. It is possible to produce a solid fuel, but the net energy gain is small since the drying process is energy demanding. The economy and the environmental impact are dependent on the fuel assumed to be replaced and the energy source for drying. System 3 seems to be viable both environmentally and economically in Karlskoga since valuable biogas used to produce process heat can be replaced and upgraded to vehicle fuel. The conclusion drawn for Karlskoga is that combustion of the residue might secure the disposal from the start, but recycling of nutrients is desirable from a sustainability perspective. It will be possible to shift the use towards (organic) fertilizer as a market develops.